Neurological Recovery Following Surgical Intervention in Patients with Traumatic Spinal Cord Injury at the University Teaching Hospital in Zambia - Munosiya Mulemwa; Joseph Lupenga; Martha Banda-Chalwe (Journal of Spine Practice)
Introduction